2010
DOI: 10.1111/j.1872-034x.2009.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of liver stiffness by interferon treatment in the patients with chronic hepatitis C

Abstract: IFN treatment reduced LS in SVR patients and relapsers. Significant reduction of LS is associated with milder fibrosis stage, lower hyaluronic acid levels, longer IFN treatment, virological response of SVR or relapse and higher alanine aminotransferase levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
79
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 48 publications
10
79
1
Order By: Relevance
“…This observation has already been made in earlier studies [35][36][37][38][39]. In our cohort, the range of changes in kPa was −4.2 to 41.8 kPa between baseline and FU24, 2.3 kPa to 29 kPa between baseline and FU96, and −2.6 to 18.7 between EOT and FU96.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…This observation has already been made in earlier studies [35][36][37][38][39]. In our cohort, the range of changes in kPa was −4.2 to 41.8 kPa between baseline and FU24, 2.3 kPa to 29 kPa between baseline and FU96, and −2.6 to 18.7 between EOT and FU96.…”
Section: Discussionsupporting
confidence: 70%
“…In the previously mentioned Arima et al study and the Chekuri et al study, no further decrease in LS was observed after treatment in long-term follow-up-no change between in LS between 1 and 2 years of follow-up [35,37]. Conversely, in the Tada et al study, as mentioned above, an LS decrease was also observed 24 weeks after therapy completion [40].…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Preliminary study results indicate that the acoustic radiation force impulse (ARFI) elastography is a noninvasive method for measuring liver stiffness (LS) and can be used for the diagnosis of liver fibrosis and cirrhosis in chronic liver disease 17, 18, 19, 20, 21, 22, 23. However, the relationship between LS and its impact on the development of HCC remains unclear in chronic hepatitis C patients who achieved SVR following DAA therapy.…”
Section: Introductionmentioning
confidence: 99%